Optimalisasi Penggunaan Energi Terbarukan untuk Desa Mandiri Energi dan Ramah Lingkungan - Nizar Amir; Makhfud Efendy; Sabarudin Akhmad; Fiki Milatul Wahyu; Rafly Firman Surya Putra (Rekayasa, 2023)
The residents of West Waru Village, Pamekasan, are renowned for their high numbers of cows, leading to a steadily increasing amount of cow dung that contaminates the environment. To combat this problem, we must find ways to utilize cow manure. There is a potential solution in the form of biogas generator technology, which can convert cow manure into energy. This research seeks to develop and optimize its design in order to provide renewable electricity for Waru Barat Village, Pamekasan. It involves the use of HOMER software to simulate and determine the optimal design. Technical, economic and environmental indicators are used as the main parameters in this research's output. The cost per kWh of generated energy stands at Rp. 1,076/kWh - a far cheaper alternative than electricity from PLN (Rp. 1,500/kWh) - making it highly beneficial for all stakeholders when constructing renewable energy power plants in rural Indonesia.